2006
DOI: 10.1152/ajpgi.00380.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-mediated inhibition of Na+/H+exchanger isoform 2 stimulates recovery of barrier function in ischemia-injured intestine

Abstract: . Prostaglandinmediated inhibition of Na ϩ /H ϩ exchanger isoform 2 stimulates recovery of barrier function in ischemia-injured intestine. Am J Physiol Gastrointest Liver Physiol 291: G885-G894, 2006. First published March 30, 2006 doi:10.1152/ajpgi.00380.2005.-Prostaglandins stimulate repair of the ischemia-injured intestinal barrier in the porcine ileum through a mechanism involving cAMP-dependent Cl Ϫ secretion and inhibition of electroneutral Na ϩ /H ϩ exchanger (NHE) activity. In the present study, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 49 publications
(69 reference statements)
1
36
0
Order By: Relevance
“…After histological analysis according Chiu et al 20 it was demonstrated that without PTX 1,13,14,16 and PGE1 [17][18][19][20] The PGE1 [17][18][19], is known by its intense vasodilator effect, for being a substance with intense biological activity that has been used for such a longtime to treat. the chronic arterial occlusive disease, since beside to vasodilation capacity it also inhibit platelets aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After histological analysis according Chiu et al 20 it was demonstrated that without PTX 1,13,14,16 and PGE1 [17][18][19][20] The PGE1 [17][18][19], is known by its intense vasodilator effect, for being a substance with intense biological activity that has been used for such a longtime to treat. the chronic arterial occlusive disease, since beside to vasodilation capacity it also inhibit platelets aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…PGE1 has a role in the activation of fibrinolysis and/ or fibrogenesis, in the modulation of cellular proliferation, in the hemorreologic activity of erithocytes, in the inhibition and activation of neutrophils capacities and also in the utilization of oxygen and glucose by the tissues. Beside to those effects there is evidence that PGE1 stimulates angiogenesis in cases of myocardic ischemia [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few reports of NHE2 affecting wound repair or cellular migration. Most notably, Blikslager et al (39,40) have shown compelling evidence that genetic elimination of NHE2 weakens recovery of mouse intestinal epithelium after ischemic damage, yet in pig, the pharmacologic inhibition of NHE2 activity strengthens ischemic recovery. The two species manifest qualitatively opposite responses in transepithelial ion permeability after addition of 25 M HOE694, and the basis for these differences remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Further, NHE2 plays a role in mucosal recovery from ischemia reperfusion. Although, whether NHE2 activity is beneficial or detrimental remains to be determined [108,107]. A role for NHE2 in salivation responses has also been observed using the NHE2 KO mice [132].…”
Section: Slc9a2 -Nhe2mentioning
confidence: 98%